ANALISIS PENGARUH KEPERCAYAAN, KEAMANAN, KUALITAS PELAYANAN, DAN PERSEPSI AKAN RISIKO TERHADAP KEPUTUSAN PEMBELIAN MELALUI SITUS JEJARING SOSIAL - Florentinus Bigar Anung Anandita Sumarno Dwi Saputra (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The purpose of this study was to analyze the significance of the effect of trust, security, quality of service and the perception of risk on purchasing decisions through social networking sites. In conclusion: There was a significant effect of trust on purchase decisions through social networking sites on college students in Surakarta. There was a significant influence on the purchase decision security through social networking sites on college students in Surakarta. There was a significant effect of service quality on purchasing decisions through social networking sites on college students in Surakarta. There is a significant effect on the perception of the risk of purchasing decisions through social networking sites on college students in Surakarta. F test analysis results it is concluded that the model used to test the effect of the independent variables are trust, security, quality of service, and the perception of risk to the dependent variable is the purchase decision through social networking sites on college students in Surakarta is right. The results of the analysis of the value of the coefficient of determination obtained Adjusted R Square = 0,535 means known that the influence exerted by the independent variables are trust, security, quality of service, and the perception of risk to the dependent variable, namely purchasing decisions through social networking sites on college students in Surakarta for while the remaining 53,5 percent. Keywords: trust, security, quality of service, perception of risk, and purchasing decisions